RAPID EFFECT OF TOCILIZUMAB IN RHEUMATOID ARTHRITIS - E Yu Panasyuk; V N Amirdzhanova; E N Aleksandrova; E G Gubar; G V Lukina; E L Luchikhina; E S Tsvetkova; T N Gavva; E F Fedorenko; A S Avdeyeva; N V Klimova; E L • Nasonov (Научно-практическая ревматология, 2011)
Objective: to evaluate the efficiency of two tocilizumab (TCZ) infusions in patients with rheumatoid arthritis (RA). Subjects and methods. The study enrolled 43 middle-aged patients with RA, mainly female ones (male/female ratio 10:33) with a RA history of 5.6±4.74 years, who were seropositive for rheumatoid factor and anti-cyclic citrullinated peptide antibodies and had high disease activity scores (DAS 28 - 6.3) prior to TCZ treatment and received disease-modifying anti-inflammatory agents, including methotrexate and glucocorticoids without providing any therapeutic effect. Therapy with TCZ was performed by the standard regimen; the dose of the drug was 8 mg/kg per infusion. The therapeutic effectiveness was evaluated 4 weeks after each infusion and by the time course of changes in DAS 28, its individual components, and health assessment questionnaire scores. Results. After the first TCZ infusion, the patients with RA were found to have significant positive changes in the major clinical and laboratory parameters of disease activity (p < 0.0001 in all cases) that progressed after the second TCZ infusion. There were reductions in DAS 28 to 4.1 and 3.1 after each infusion and in the number of patients with high disease activity and an increase in that of patients with low/moderate one. At the same time, more than 20% of the patients developed remission after the second infusion. A good therapeutic effect was noted in 14 and 51% of the patients after the first and second infusions, respectively. Conclusion. TCZ exerts a rapid statistically significant positive effect on the major clinical and laboratory parameters of RA activity.